Pengaruh Komposisi Tandan Kosong Kelapa Sawit dan Bungkil Inti Kelapa Sawit sebagai Pakan Larva Lalat Tentara Hitam (Hermetia Illucens) Terhadap Perubahan Kandungan Asam Lemaknya - Muhammad Edwin Syahputra Lubis; Brahmani Dewa Bajra; Ilmi Fadhilah Rizki; Manda Edy Mulyono; Bagus Giri Yudanto; Frisda Rimbun Panjaitan (Jurnal Penelitian Kelapa Sawit, 2023)
Oil palm empty fruit bunches (OPEFB) and Palm Kernel Meal (PKM) are the most abundant by product in palm oil industry. However, the optimal utilization of both substrate has not yet discovered. This is due to high lignocellulosic content in OPEFB contains high lignocellulose content, on the other hand, PKM contains high crude protein content, High lignocellulose content of OPEFB causes this particular substrate to be hard to decompose, while lignin and crude protein content in PKM requires it to be pretreated prior to utilization. Black Soldier Fly (BSF, Hermetia illucens) is a natural bioreactor that is able to convert biomass into high value insect protein, fats, and chitin. BSF fats is highly potential to be used as high valued product, such as animal feed and biofuel. However, research that utilize OPEFB and PKM to modulate BSF fatty acid content during its' vegetative state is scarce. This study shows that inclusion of OPEFB as the dominant composition of the BSF feed modulate the synthesis and accumulation of lauric acid. Whilst the feed with PKM as dominant composition tends to modulate the synthesis of n-3 fatty acid, thus lowering the n-6/n-3 ratio of BSF fats. This research confirm the plasticity of BSF fats fatty acid composition depends on both feed fatty acid composition and digestability.Present study shows the potential of BSF utilization to valorize oil palm biomass into highly valuable specific fats sustainably.